Study on superluminescent diodes using InGaAs-InAs chirped quantum dots - Han, IK; Heo, DC; Song, JD; Lee, JI (KOREAN PHYSICAL SOC, 2004)
We have fabricated superluminescent diodes (SLD) by using InGaAs-InAs chirped quantum dots (QD). The spectral bandwidth of the SLD was measured to be 170 nm. These results explain the possibility of QD-based SLD exceeding the performance of multi-quantum well-based ones.